2021
DOI: 10.21203/rs.3.rs-692503/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification Hub Genes of Consensus Molecular Subtype Correlation with Immune Infiltration and Predict Prognosis in Gastric Cancer

Abstract: Gastric Cancer (GC) has a great fatality rate, meanwhile, there is still a lack of available biomarkers for prognosis. The goal of the research was to discover key and novel potential biomarkers for GC. We screened for the expression of significantly altered genes based on survival rates from two consensus molecular subtypes (CMS) of GC. Subsequently, functional enrichment analysis showed these genes involved in many cancers. And we picked 6 hub genes that could both secreted in the tumor microenvironment and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…[11,12] Moreover, CHRDL1 has been identified as a potential biomarker for cancer prognosis, including gastric cancer (GC) and THCA. [13,14] Besides, the mechanisms of CHRDL1 in some cancers have been reported. Wang et al found that CHRDL1 expression was regulated by hsa-mi-croRNA-204 expression, which affected the invasion and proliferation of GC cells.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Moreover, CHRDL1 has been identified as a potential biomarker for cancer prognosis, including gastric cancer (GC) and THCA. [13,14] Besides, the mechanisms of CHRDL1 in some cancers have been reported. Wang et al found that CHRDL1 expression was regulated by hsa-mi-croRNA-204 expression, which affected the invasion and proliferation of GC cells.…”
Section: Introductionmentioning
confidence: 99%